(untitled) (The Strategic Review for Southern Africa, 2020)
The South African National Development Plan envisions a capable democratic developmental state as the only response to the country’s deteriorating triple challenges of unemployment, poverty and inequality. A developmental state denotes a development theory that advocates for a state-led development model to accelerate economic growth and rapid industrialisation. However, most successful developmental states were led by authoritarian regimes. The rise of democracy within emerging and developing economies invokes a different kind of developmental state model, based on democratic development and the active role of subnational governments. Despite subnational governments playing a key role in democratic development, there is limited literature on the role of subnational institutions in building and consolidating democratic developmental states. This article analyses the role and contribution of subnational institutions in strengthening South Africa’s emerging democratic developmental state through developmental local government. It argues that developmental local government is underpinned by the structural and developmental ideology of a (democratic) developmental state. The article further illustrates how critical features such as maximising social and economic development; promoting democratic development; integrating and coordinating development; and building social capital are used to consolidate South Africa’s emerging democratic developmental states from below.